2007
DOI: 10.1007/s11829-006-9000-1
|View full text |Cite
|
Sign up to set email alerts
|

Visual ecology of aphids—a critical review on the role of colours in host finding

Abstract: We review the rich literature on behavioural responses of aphids (Hemiptera: Aphididae) to stimuli of different colours. Only in one species there are adequate physiological data on spectral sensitivity to explain behaviour crisply in mechanistic terms. Because of the great interest in aphid responses to coloured targets from an evolutionary, ecological and applied perspective, there is a substantial need to expand these studies to more species of aphids, and to quantify spectral properties of stimuli rigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
229
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(238 citation statements)
references
References 84 publications
(89 reference statements)
9
229
0
Order By: Relevance
“…These aphid preferences were likely mediated by plant-derived olfactory and visual cues, as aphids are known to use both to locate host plants while walking [43][44][45]. Both plant volatile emissions and leaf-colour profiles were also altered to a much greater extent by ZYMV than by WMV, whereas mixed infections elicited a phenotype similar to that exhibited by plants with single ZYMV infections (see figure 2a and electronic supplementary material, S1 and S2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These aphid preferences were likely mediated by plant-derived olfactory and visual cues, as aphids are known to use both to locate host plants while walking [43][44][45]. Both plant volatile emissions and leaf-colour profiles were also altered to a much greater extent by ZYMV than by WMV, whereas mixed infections elicited a phenotype similar to that exhibited by plants with single ZYMV infections (see figure 2a and electronic supplementary material, S1 and S2).…”
Section: Discussionmentioning
confidence: 96%
“…more intense yellow coloration) and reduction of the blue component (which was also observed for single WMV infections; electronic supplementary material, figure S1). Aphids typically exhibit a preference for yellow and an aversion to blue to ultraviolet coloration (reviewed in Doering & Chittka [43]). …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it has been suggested that aphids use the ratio between long and short wavelength light to navigate between plants rather than responding to only the one or the other (Kennedy et al 1961;Kennedy & Booth 1963). Döring & Chittka (2007) also argued that the yellow preference shown by aphids should not be viewed as a true colour preference but rather a response that is dependent on the actual light intensity. The yellow preference observed for some aphid species, including summer morphs of R. padi, may be due to yellow representing a superfoliage stimulus to herbivorous insects rather than it being an ecological adaptation (Prokopy & Owens 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the role of visual stimuli in aphid host plant selection behaviour could lead to improved aphid management, e.g. choice of trap colour and colour intensities for aphid monitoring and use of light reflectance to manage aphid-transmitted plant viruses (Döring & Chittka 2007). Many aphid species preferentially respond to yellow targets, and yellow traps are frequently used for aphid monitoring (Broadbent 1948;Heathcote 1957).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation